Factors Associated With Ulcer Healing and Quality of Life in Patients With Diabetic Foot Ulcer. (March 2017) - Spanos, Konstantinos; Saleptsis, Vasileios; Athanasoulas, Athanasios; Karathanos, Christos; Bargiota, Alexandra; Chan, Philip; Giannoukas, Athanasios D.
A prospective nonrandomized cohort study on consecutive diabetic patients with foot ulcer was undertaken to assess the factors associated with the healing process or limb salvage and evaluate the impact of their treatment on their quality of life. Quality of life was evaluated using Diabetic Foot Ulcer Scale–Short Form (DFS-SF) questionnaire before and after treatment. A total of 103 diabetic patients with ulcer (mean age 69.7 ± 9.6 years, 77% male) were treated and followed up for 12 months. Ulcer healing, minor amputation, and major amputation rates were 41%, 41%, and 18%, respectively, while the mortality rate was 18%. Ulcer healing was associated with University of Texas wound grade 1 and the Study of Infections in Diabetic feet comparing Efficacy, Safety and Tolerability of Ertapenem versus Piperacillin/Tazobactam trial's diabetic foot infection wound score. Limb loss was associated with nonpalpable popliteal artery, longer in-hospital stay, and delay until referral. Quality of life was improved in all domains of DFS-SF ( P < .0001) throughout the cohort of our patients regardless of their outcome, and no outcome (healing, minor amputation, or major amputation) was superior to other. Significant improvement was observed in all domains of hygiene self-management after consultation during the follow-up period.